Visible-Light Bismuth Iron Molybdate Photocatalyst for Artificial Nitrogen Fixation. Issue 5 (1st January 2019) - Liu, Botong; Yasin, Alhassan S.; Musho, Terrence; Bright, Joeseph; Tang, Haibin; Huang, Ling; Wu, Nianqiang
Abstract : The vast majority of semiconductors photocatalysts reported for artificial nitrogen fixation have a large bandgap at around 3.0 eV, thus photocatalytic nitrogen reduction is driven mainly by ultraviolet light. In contrast, this report demonstrates for the first time that bismuth iron molybdate (Bi3 FeMo2 O12 ) with a bandgap of 2.25 eV exhibits visible-light photocatalytic activity toward nitrogen-to-ammonia conversion. Furthermore, introduction of oxygen vacancy to this photocatalyst increases the ammonia production rate remarkably. Density functional theory (DFT) calculation reveals that the oxygen vacancies help adsorb and stabilize the N-H intermediate species, and lower the energy barrier of intermediate reactions. This work has an implication in design of semiconductor photocatalysts for sustainable ammonia synthesis under the ambient condition using solar energy.